PERENCANAAN SISTEM INFORMASI STARTEGIS MEGGUNAKAN METODE EAP PADA RS SAKIT KESREM LHOKSEUMAWE - Akbar, Anggi Rizki; Yulisda, Desvina; Fitria, Rahma (Smart Education, 2025)
Abstract: Strategic information system planning is an important process to combine business strategy with information technology needs, especially in the field of health services. The purpose of this research is to use the Enterprise Architecture Planning (EAP) approach to design an integrated strategic information system at Kesrem Lhokseumawe Hospital. EAP includes stages such as planning initialisation, business modelling, analysis of current systems and technologies, design of data architecture, application architecture, and technology architecture, and preparation of a system implementation plan. The analysis results show that business activities at Kesrem Hospital are divided into two main categories: medical and nursing services; and supporting categories, such as financial management, human resources, and infrastructure facilities. The current information system is still manually created and not integrated, which causes data errors and high delays in decision-making. The identification of key data entities, list of candidate applications based on business functions, proposed network topology, and prioritised application implementation roadmap are all part of the resulting architecture design. It is expected that this strategic planning serves as a model for building information systems that are flexible, effective, and capable of assisting data-driven and rapid management decision-making.Keyword: Strategic Information System Planning; Enterprise Architecture Planning (EAP); Hospital; Data Architecture; Application Portfolio.Abstrak: Perencanaan sistem informasi strategis adalah proses penting untuk menggabungkan strategi bisnis dengan kebutuhan teknologi informasi, khususnya dalam bidang layanan kesehatan. Tujuan dari penelitian ini adalah untuk menggunakan pendekatan Enterprise Architecture Planning (EAP) untuk membuat rancangan sistem informasi strategis yang terintegrasi di Rumah Sakit Kesrem Lhokseumawe. EAP mencakup tahapan seperti inisialisasi perencanaan, pemodelan bisnis, analisis sistem dan teknologi yang sedang berjalan, perancangan arsitektur data, arsitektur aplikasi, dan arsitektur teknologi, dan penyusunan rencana implementasi sistem. Hasil analisis menunjukkan bahwa aktivitas bisnis di RS Kesrem terbagi menjadi dua kategori utama: pelayanan medis dan keperawatan; dan kategori pendukung, seperti manajemen keuangan, sumber daya manusia, dan sarana prasarana. Sistem informasi saat ini masih dibuat secara manual dan tidak terintegrasi, yang menyebabkan kesalahan data dan keterlambatan pengambilan keputusan yang tinggi. Identifikasi entitas data utama, daftar calon aplikasi berdasarkan fungsi bisnis, usulan topologi jaringan, dan roadmap implementasi aplikasi prioritas adalah semua bagian dari rancangan arsitektur yang dihasilkan. Diharapkan perencanaan strategis ini berfungsi sebagai model untuk membangun sistem informasi yang fleksibel, efektif, dan mampu membantu pengambilan keputusan manajemen yang berbasis data dan cepat.Kata kunci: Perencanaan Sistem Informasi Strategis; Enterprise Architecture Planning (EAP); Rumah Sakit; Arsitektur Data; Portofolio Aplikasi.